OVERVIEW METODE PERHITUNGAN KERENTANAN AIRTANAH TERHADAP RENCANA PENAMBANGAN - SHENNY LINGGASARI; Tedy Agung Cahyadi; Rika Ernawati (Retii, 2019)
ABSTRACT Mining activities have many impacts, one of them is changes of land use. The effect of land use affects the potential for water absorption which will have an impact on the availability of groundwater both in quantity and quality. The reduction in groundwater potential in the mining area is very possible because the elevation of the mine openings will be below the surface of the ground, especially the surface of the groundwater. This reduction in groundwater potential will affect the decrease in groundwater level, groundwater discharge, and decrease in land surface which can cause pollution. Therefore, it is necessary to analyze the vulnerability of groundwater to become a reference in groundwater management. The method of analyzing groundwater vulnerability has grown quite a lot in recent years. To find out the groundwater vulnerability method that is suitable for the mining plan, the authors compare several methods by looking at their strengths and weaknesses based on literature studies. The method of analyzing groundwater vulnerability to the mining plan aims to determine the potential for pollution and as a reference in making mining facilities and infrastructure. The SI and DRASTIC method is the most suitable method for determining vulnerability of groundwater groundwater for a mining plan. Keywords: vulnerability, groundwater, methods, mining, drastic.